2002
DOI: 10.1590/s1415-65552002000300008
|View full text |Cite
|
Sign up to set email alerts
|

Os fatores que motivam a adoção da terceirização da Tecnologia de Informação: uma análise do setor industrial de São Paulo

Abstract: O objetivo desse artigo é identificar os principais fatores que motivam a terceirização de serviços da área de Tecnologia de Informação. O texto apresenta inicialmente a definição utilizada de terceirização e um modelo de referência útil para a sua avaliação. Em seguida se apresenta a metodologia de pesquisa, a descrição das variáveis e os resultados da pesquisa. No final são apresentadas as conclusões do trabalho. Para atingir esses objetivos foram pesquisadas 100 empresas do setor industrial do Estado de São… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
15

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 2 publications
1
3
0
15
Order By: Relevance
“…Similar results were found by Prado and Takaoka (2002) studying the outsourcing of software development. The authors identified some important drivers for this process: cost reduction, access to knowledge and technology, routine activities, seasonal works and the high degree of customization.…”
Section: E E E Evolution and Volution And Volution And Volution And Ssupporting
confidence: 86%
“…Similar results were found by Prado and Takaoka (2002) studying the outsourcing of software development. The authors identified some important drivers for this process: cost reduction, access to knowledge and technology, routine activities, seasonal works and the high degree of customization.…”
Section: E E E Evolution and Volution And Volution And Volution And Ssupporting
confidence: 86%
“…According to Clark et al (1995) andDe Looff (1997), the cost is the most important motivator of outsourcing due to the growth of the budget brought about by greater use of IT. And the dominant thinking that guides the current methodologies for suppliers selection of IT services, as Prado and Takaoka (2002), Reinhard and Bergamaschi (2008) and Meireles (2007), focuses, primarily, on the lowest price of the service and/or reduction the total value of IT services.…”
Section: Methodsmentioning
confidence: 99%
“…It is clear that technological evolution contributes to the growth of outsourcing as many products and IT services have become commodities and allowed the companies to obtain economies of scale through external suppliers. (Meireles, 2007) Prado and Takaoka (2002) concluded that there are seven main motivating factors for outsourcing in industrial enterprises from São Paulo, considering that cost reduction and access to knowledge and technology are the two more relevant factors.…”
Section: It Outsourcing In Brazilmentioning
confidence: 99%
“…De acordo com Prado & Takaoka (2002), os contratos de terceirização podem ser contratos de incentivo, mais baseados em expectativas de que tanto o cliente como o fornecedor vão realizar negócios por vários anos. Klepper & Jones (1998) observaram que, apesar de a terceirização trazer benefícios, existem também custos e riscos a ser considerados.…”
Section: Estratégia De Terceirização De Sistemas De Informaçãounclassified